Mental time travel and retirement savings - David Blake; John Pickles (Journal of Risk and Financial Management, 2021)
We portray the valuation of retirement savings in terms of a mental time travel journey in which a proposed contribution to a pension plan is projected forward to the plan member's retirement date and this projected value is then discounted back to today, thereby giving a present or personal value. We set this within a broader framework of pension planning, which seeks to smooth consumption over the lifecycle. We explain how two psychological biases-exponential growth bias and present bias-can lead to a difference between the initial value of a pension contribution and its present value, such a difference reflecting an asymmetry between projection and discounting, and how such a difference might lead to inadequate retirement savings and hence to a lower than desired standard of living in retirement. We consider how the two biases might be mitigated.
Keywords: G04; G51; 330; retirement savings; lifecycle model; financial investment valuation; mental time travel; time perception; projecting; exponential growth bias; discounting; present bias; symmetric; asymmetric; valuation